Volatile flavor compounds of gamma irradiated Cucumis sativus L. (cucumber) seeds by simultaneous distillation extraction and gas chromatography-mass spectrometry analysis - Showkat, Warda Nazneen; Khan, Naeem; Jamila, Nargis; Nishan, Umar; Minhaz, Aaliya; Dad, Waseem; Choi, Ji Yeon; Ibrahim, Mohamed A.; Kim, Kyong Su (Penerbit Universiti Kebangsaan Malaysia, 2024)
Food irradiation is a technique applied to increase food safety and prolongs shelf life. Irradiation with gamma rays is one of the sterilization and preservation methods used in the food industry. The current study was aimed at analyzing the volatile flavor compounds of Cucumis sativus L. seeds and to assess the impact of gamma irradiation on these flavor compounds. The Cucumis sativus (cucumber) seeds were gamma irradiated with 1, 5, 10, and 20 kGy doses and analyzed for flavor profile compounds. Simultaneous distillation extraction (SDE) and gas chromatography mass spectrometry (GC-MS) techniques were used to determine the volatile flavor compounds. From the results, a total of 58 volatile compounds in the non-irradiated (control) sample were identified with 1-hexanol (13.2%), methyl valerate (8.97%), and butanoic acid, methyl ester (8.34%) as the most abundant compounds. Among the 58 volatile flavor compounds identified, 23 were those detected in varying quantities in all irradiated samples and non-irradiated control. The number of flavor compounds increased with increasing irradiation doses, from 1 kGy to 10 kGy and then decreased at 20 kGy. The results indicated that high dose of radiation (above 10 kGy) has direct impact on concentration and profile of volatile flavor compounds. Conclusively, gamma-irradiation up to 10 kGy doses can be employed for food sterilization to increase shelf life of analyzed seeds.